Odpowiedzialność sprawców wykorzystywania seksualnego małoletnich poniżej lat 15 w kontekście znamion przestępstwa z artykułu 197 Kodeksu karnego - Malinowska-Bizon, Aleksandra (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The purpose of this article is to present the difficulties in collecting evidence during preparatory and judicial proceedings concerning sexual violence against young children, in particular rape, in the light of existing legal solutions, that is the elements of the prohibited act stated in Article 197 of the Polish Criminal Code. The author points to the discrepancies in the definitions of rape functioning in Polish law and those found in international conventions and the judicial practice of the European Court of Human Rights, suggesting a departure from the traditional and literal interpretation of the elements that constitute the prohibited act of rape.